Impact of rheumatoid arthritis in Turkey: a questionnaire study - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2014)
Objective Unmet needs of rheumatoid arthritis (RA) patients regarding physician/patient communication, treatment preferences and quality of life issues were investigated in a Turkish survey study. Methods The study was conducted with the contribution of 33 rheumatologists, and included 519 RA patients. The study population included patients who had been on biologic therapy for >6 months and were still receiving biologic therapy (BT group), and those who were biologic naive, but found eligible for biologic treatment (NBT group). Of the RA patients, 35.5% initially had a visit to an internal disease specialist, 25.5% to a physical therapy and rehabilitation specialist, and 12.2% to a rheumatology specialist for their RA complaints. The diagnosis of RA was made by a rheumatologist in 48.2% of patients. Results The majority of RA patients (86.3%) visit their doctor within 15-week intervals. Most of the physician-patient communication focused on disease symptoms (99.0%) and impact of the disease on quality of life (61.8%). The proportion of RA patients who perceived their health status as good/very good/excellent was higher in the BT group than in the NBT group (74.3% vs. 51.5%, p<0.001). However, of those RA patients in the NBT group, only 24.8% have been recommended to start a biologic treatment by their doctors. With respect to dose frequency options, once-monthly injections were preferred (80%) to a bi-weekly injection schedule (8%). Conclusion In conclusion, RA patients receiving biologic therapy reported higher rates of improved symptoms and better quality of life and seemed to be more satisfied with their treatment in our study.
Keywords: rheumatoid arthritis; quality of life; patient survey; TREATMENT ALGORITHM; THERAPY; BIOLOGICS; OUTCOMES; REGISTRY; CARE